1987
DOI: 10.1111/j.1365-2621.1987.tb14021.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Milk on Mineral Precipitation by Na Phytate

Abstract: Sodium phytate was added to milk with and without the addition of Fe or Zn and the solubility of the endogenous Ca and added Fe or Zn was not affected. However, when these experiments were repeated with a model system containing CaC12 at the same calcium concentration as milk, the addition of Na phytate caused a significant precipitation of each of these minerals. These results suggest that milk exerts a protective effect on the phytate induced precipitation of these minerals and thus their potential bioavaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The magnitude of effect of each two previous factors can not be clearly isolated. Hence, it may be concluded that the mechanism of impairing the absorption of monovalent minerals has mainly proceeded through physical action i. e. the elastic gels fo the highly esterified pectins favoured hosting the small monovalent ions between the loosely crosslinked pectin chains in accordance with the previous observations of Platt and Clydesdale [23]. During the movement of digested food from the acidic condition in the stomach to the intestine, the pH may lay within the range optimal for gel formation.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The magnitude of effect of each two previous factors can not be clearly isolated. Hence, it may be concluded that the mechanism of impairing the absorption of monovalent minerals has mainly proceeded through physical action i. e. the elastic gels fo the highly esterified pectins favoured hosting the small monovalent ions between the loosely crosslinked pectin chains in accordance with the previous observations of Platt and Clydesdale [23]. During the movement of digested food from the acidic condition in the stomach to the intestine, the pH may lay within the range optimal for gel formation.…”
Section: Resultssupporting
confidence: 76%
“…In conclusion, it is remarked in the most cases that the degree of esterification and not the amount of free carboxyl groups is more determinant of the mineral binding in accordance with Platt and Clydesdale [23]. Hence, pectins may be useful in counteracting heavy metals poisoning.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations